قياس إستقرار الأداء المالي للبنوك الإسلامية في ظل الأزمة المالية العالمية لسنة 2008م - دراسة تطبيقية لمجموعة من البنوك الإسلامية لبعض الدول العربية- - برابح, دلال (Université de M'sila, 2018)
تناولت هذه الأطروحة دراسة موضوع " قياس الاستقرار المالي للبنوك الإسلامية في ظل الأزمة المالية العالمية لسنة 2008-دراسة تطبيقية لعينة من البنوك الإسلامية-"، وذلك بهدف معرفة مدى تأثر البنوك الإسلامية بالأزمة المالية العالمية لسنة 2008.ومن أجل ذلك تم تقسيم موضوع الدراسة إلى أربعة فصول، حيث تناولنا في الفصل الأول، مدخل عام إلى البنوك الإسلامية أما الفصل الثاني جاء بعنوان قراءة في الأزمة المالية العالمية لسنة 2008 م، أما الفصل الثالث تطرقنا فيه لدراسة الاستقرار المالي وإدارة المخاطر المالية في البنوك الإسلامية، أما الفصل الرابع والأخير تعرضنا فيه الى الدراسة الميدانية وذلك من خلال تطبيق نموذج sherrod على مجموعة من البنوك الإسلامية في ظل الأزمة المالية العالمية لسنة2008 م.وفي الأخير توصلنا إلى جملة من النتائج نذكر أهمها فيما يلي: تبين أن من أبرز أسباب الأزمة المالية العالمية لسنة 2008م منافية لمبادئ الشريعة الإسلامية كالربا وتوريق ديون الرهن العقاري غير المضبوط، إضافة إلى ذلك فلسفة التوسع في الدين والإنفاق، إضافة إلى أن أسس الهندسة المالية التقليدية المنبثقة من فلسفة المذهب الاقتصادي الرأسمالي الحر لها الأثر الأكبر فيما حصل، وتعد البنوك الإسلامية بمثابة مؤسسات مالية تزاول النشاط المصرفي والاستثماري في ظل تعاليم الإسلام، وفي حدود نطاق الضوابط الشرعية الإسلامية فقد انتشرت البنوك الإسلامية بشكل واسع بحيث لم تقتصر فقط على البلدان الإسلامية بل امتدت إلى البلدان غير الإسلامية. This thesis deals with the study of the measurement of the financial stability of Islamic banks in light of the global financial crisis for 2008, an applied study of a sample of Islamic banks, in order to determine the impact of Islamic banks on the global financial crisis of 2008.For this end we devide our study in four chapters ,in Chapter 1, we present a general introduction to Islamic banks. The second chapter we discussed the global financial crisis for 2008.The third chapter deals with the study of financial stability and risk management in Islamic banks. , And the fourth and last chapter, where we presented to the field study through the application of the model sherrod on a sample of Islamic banks in light of the global financial crisis for the year 2008.Finally, we reached a number of results, the most important of which are the following: It turned out that one of the most prominent causes of the global financial crisis in 2008 Contrary to the principles of Islamic Sharia, such as usury,Securitization of unconsolidated mortgage debt,In addition to the philosophy of expansion in debt and spending, in addition to the foundations of traditional financial engineering emanating from the philosophy of free economic economic doctrine has the greatest impact in what happened, and Islamic banks are financial institutions engaged in banking and investment under the teachings of Islam, and within the limits of Islamic Shariah Islamic banks have spread so widely that they were not limited to Islamic countries but extended to non-Muslim countries